Latent class analysis for health-related quality of life in nurses in China - Yan Zhao; Bei Yang; Jianying Chu; Jianying Chu (Frontiers in Public Health)
BackgroundThis study aimed to identify the types of quality of life (QoL) based on the five dimensions of the EQ-5D and predict factors affecting QoL.MethodsA multistage stratified cluster sampling survey was conducted among the staff of 12 general hospitals, 1,965 nurses completed the survey, and the data were analyzed using SPSS 26.0 and Mplus 8.3 for latent analysis.ResultsThree latent classes of QoL were identified: low-level (2.8%), pain and discomfort (7.6%), medium-level (47.1%), and high-level (42.5%). The types and characteristics of QoL differed among these latent classes. The low-level group had the lowest EQ visual analog scale (EQ-VAS) score (F = 75.217, P < 0.001) and the highest K10 score (F = 61.90, P < 0.001). Moreover, increased age (OR = 0.819, 95% CI: 0.817–0.973), never having drunk alcohol (OR = 0.107, 95% CI: 0.023, 0.488), and increased EQ-VAS scores (OR = 0.935, 95% CI: 0.919, 0.952) were protective factors for quality of life, while working in obstetrics and gynecology (OR = 6.457, 95% CI:1.852, 22.512) and higher K10 scores (OR = 1.153, 95% CI: 1.100, 1.209) were risk factors for quality of life.ConclusionThe results indicated significant heterogeneity in the types of QoL and identified predictors of QoL. These findings provide basic information for the development of nursing interventions to improve quality of life and identified specific characteristics that should be considered during intervention development.